2018
DOI: 10.1200/po.17.00160
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Evolution of Resistance to ALK Tyrosine Kinase Inhibitors Through Longitudinal Analysis of Circulating Tumor DNA

Abstract: Purpose ALK rearrangements predict for sensitivity to ALK tyrosine kinase inhibitors (TKIs). However, responses to ALK TKIs are generally short-lived. Serial molecular analysis is an informative strategy for identifying genetic mediators of resistance. Although multiple studies support the clinical benefits of repeat tissue sampling, the clinical utility of longitudinal circulating tumor DNA analysis has not been established in ALK-positive lung cancer. Methods Using a 566-gene hybrid-capture next-generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 25 publications
2
77
1
Order By: Relevance
“…NGS, the results for which are usually expressed as allele frequency, has the potential to become widely adopted for liquid biopsy analysis because it is able to simultaneously identify various genetic alterations including those responsible for resistance to targeted therapy. [24][25][26][27][28][29][30][31] Our findings suggest that the monitoring of allele frequency for EGFRactivating mutations in cfDNA by NGS may also be useful for the prediction of EGFR-TKI treatment efficacy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…NGS, the results for which are usually expressed as allele frequency, has the potential to become widely adopted for liquid biopsy analysis because it is able to simultaneously identify various genetic alterations including those responsible for resistance to targeted therapy. [24][25][26][27][28][29][30][31] Our findings suggest that the monitoring of allele frequency for EGFRactivating mutations in cfDNA by NGS may also be useful for the prediction of EGFR-TKI treatment efficacy.…”
Section: Discussionmentioning
confidence: 77%
“…Such a pattern was also evident for the allele frequency of EGFR ‐activating mutations (the ratio of the number of activating mutations to the total number of EGFR alleles) as determined by ddPCR (data not shown). NGS, the results for which are usually expressed as allele frequency, has the potential to become widely adopted for liquid biopsy analysis because it is able to simultaneously identify various genetic alterations including those responsible for resistance to targeted therapy . Our findings suggest that the monitoring of allele frequency for EGFR ‐activating mutations in cfDNA by NGS may also be useful for the prediction of EGFR‐TKI treatment efficacy.…”
Section: Discussionmentioning
confidence: 83%
“…This result is similar to other studies reporting between 44 and 56% of patients with kinase domain mutations. 10,27,37,38 Notably, seven of the 16 (43.8%) patients with resistance mutations in ALK demonstrated more than one mutation. This contrasts with a recently published series of ALK positive patients who underwent tissue-based NGS after progression on second generation ALKi in which 6/48 (12%) patient specimens contained compound mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Small studies, such as a recent report that identified two cfDNA ALK fusions in a cohort of 102 patients show that the detection of these alterations is feasible, albeit more technically challenging than somatic mutation detection, while a longitudinal evaluation of 22 patients was able to detect ALK fusions in 86% at progression. 18,23,2527 Additionally, although numerous tumor-tissue based studies have demonstrated mechanisms of resistance to ALKi, the use of cfDNA for the evaluation of drug resistance mechanisms in ALK -positive NSCLC has not been published.…”
Section: Introductionmentioning
confidence: 99%
“…In future research, we will explore the underlying mechanism for this result. Because NGS technology has displayed impressive capability for identifying the underlying molecular profile of cancers, its clinical application as a molecular screening test might favorably alter the clinical outcomes of ALK ‐positive NSCLC patients …”
Section: Discussionmentioning
confidence: 99%